1995
DOI: 10.1183/09031936.95.08121993
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of gas exchange in liver cirrhosis

Abstract: even at rest when TL,CO falls below about 50% of predicted, and Agustí's patients did not have pulmonary vascular malformations. Perhaps the subject of Crawford's study has lung disease in addition to vascular malformations, and both contribute to the hypoxaemia. Interpretation of radiolabelled particle distributionThe authors used albumin aggregates whose diameters were stated to range from 15 µm to 50 µm. Assuming radioactivity relates to particle mass, not diameter, 50 µm particles would be 37 times hotter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Pa,O 2 w40 kPa (w300 mmHg)) observed in many patients. Diffusion impairment to oxygen, as shown by a greater predicted (according to the multiple inert gas elimination technique) [42] than measured Pa,O 2 [40,41] while breathing room air, is also present in advanced HPS, a mechanism also consistent, in part, with the common finding of a low diffusing capacity of the lung for carbon monoxide (DL,CO). It is of note that the presence of an elevated Q9 facilitates, in part, this favourable Pa,O 2 response to breathing 100% oxygen, other things being equal.…”
Section: Pathophysiologymentioning
confidence: 64%
See 1 more Smart Citation
“…Pa,O 2 w40 kPa (w300 mmHg)) observed in many patients. Diffusion impairment to oxygen, as shown by a greater predicted (according to the multiple inert gas elimination technique) [42] than measured Pa,O 2 [40,41] while breathing room air, is also present in advanced HPS, a mechanism also consistent, in part, with the common finding of a low diffusing capacity of the lung for carbon monoxide (DL,CO). It is of note that the presence of an elevated Q9 facilitates, in part, this favourable Pa,O 2 response to breathing 100% oxygen, other things being equal.…”
Section: Pathophysiologymentioning
confidence: 64%
“…However, the relative contributions of the former three determinants appear to vary. Although it is agreed that V9A/Q9 mismatching is the pivotal mechanism for arterial deoxygenation since it fits well with the presence of lung regions in which alveoli are normally ventilated but overperfused, the relevance of the other two factors remains somewhat speculative [41]. An added conceptual difficulty is the reconciliation of the presence of elevated levels of increased intrapulmonary shunt (i.e.…”
Section: Pathophysiologymentioning
confidence: 96%
“…The magnitude of the shunt can be estimated by calculating the ratio of systemic to total body radioactivity. Estimations obtained using this method exceed by far the functional estimates provided by the oxygen method [64,66,76]. This may be because dilated intrapulmonary vessels may continue to participate in gas exchange, especially when the driving pressure is increased by the administration of pure oxygen.…”
Section: Diagnosismentioning
confidence: 71%
“…Other mechanisms, such as decrease in the affinity of haemoglobin for oxygen and portopulmonary shunt, have been essentially dismissed as causes of severe hypoxaemia in HPS [63]. However, CRAWFORD et al [65] and WAGNER [66] have recently highlighted the complexity of hypoxaemia caused by cirrhosis and suggested that we still do not have the tools to understand fully its mechanism.…”
Section: Mechanism Of Hypoxaemiamentioning
confidence: 99%
“…As with other lung disorders, hypoxaemia results from impaired gas exchange, which, in HPS, is particularly perturbed by excessive and widespread dilatation of intrapulmonary vessels. After decades of careful investigations, the underlying mechanisms linking altered gas exchange and pulmonary vasodilatation are now well delineated [2][3][4]. Reduced tone causing vascular relaxation occurs at both ends of the capillary bed, i.e.…”
mentioning
confidence: 99%